(untitled) (Research, Society and Development, 2020)
The waste of fruits often occurs due to not knowing how to store them correctly, causing rot and early ripening, being discarded. Therefore, the ideal storage for each fruit purchased is essential to avoid waste and increase the consumption of these foods. With this, the objective of the study was to verify through a longitudinal research of qualitative character, how four different ones of banana, apple, papaya and persimmon modify indexes of the content of soluble solids, pulp firmness and internal and external color after 9 days submitted and stored under refrigeration (14ºC) and at room temperature (22ºC), in order to evaluate the best storage after commercialization. During the analysis, you can see great changes in the fruits, the banana had a decrease in firmness when not refrigerated and in the contents of soluble solids when refrigerated. During the days the papaya brought great differences such as its level of firmness, which declined significantly when not refrigerated, but became 4 times firmer when refrigerated. Soluble solids decayed at room temperature bringing a bitterness due to the rotting of the fruit, and the color, much darker when compared to chilled papayas.